(3GdbGehS GdaGFV aj Yde GdaQGFVs - (3CMeO Hf jMji Hf GdeQJVi Hf GdeaVd GHf efUhQ GdMSfj, J (B840 (3g`s ((3CMeO Hf YHO Gddg GdTQai s)
(3ChdgG (B:s
(3ebOeI ai HjGf SHH GdJhQK heGfYg aUd (B: (3ehLH GdEQK fSH Ch fcGM Ch hdGA s
(3BNQgG (B:s
(3aEf JQc HfJkG MQI hGHfkG YJb Je cJGH Hef Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3cJHJ GdYfhGfGJ HGdMeQIs
(3cJHgG GdfGSN ddbGVi LeGd GdOjf Ydi Hf CMeO Hf OGhO GdeUQis
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3Gdabg GdESdGejs